Stones to stains : the drawings of Victor Hugo - Burlingham, Cynthia, 1955-; Pesenti, Allegra; Rodari, Florian; Hammer Museum (Los Angeles, CA : Hammer Museum, University of California, Los Angeles ; Munich ; New York : DelMonico Books-Prestel, 2018)
"Exhibition catalogue accompanying the exhibition, Stones to Stains: The Drawings of Victor Hugo, on view at the Hammer Museum September 27-December 30, 2018"--
boek
Keywords: Hugo, Victor, -- 1802-1885 -- Exhibitions; ART / Individual Artists / Monographs; ART / History / Baroque & Rococo; ART / History / Modern (late 19th Century to 1945).